The Natural Hand Sanitizer Stamping Dispenser KKN Covid 19 UNS Bumirejo Village, Kecamatan Kebumen, Kabupaten Kebumen - Budi Legowo (Universitas Sebelas Maret, 2020)
UNS Covid19 KKN is a Thematic KKN held by Sebelas Maret University which was held in an individual format during the pandemic period. A total of 20 students were included in the Group of 87 KKN Covid19 UNS Batch 2 with a service area in Kebumen Regency. The implementation of appropriate technology for the stamping model of the dispenser with natural hand sanitizer aims to reduce the risk of spreading the virus from hand to hand. The stamping model dispenser was made of PVC as the main ingredient, and natural hand sanitizer was made from a mixture of betel and lime leaves. Four sets of tools were distributed in places of worship, mosques / prayer rooms in Bumirejo Village, Kebumen District, Kebumen Regency. The results of the program evaluation showed the public's appreciation of the appropriate technology made. The production cost for the dispenser was still quite expensive, so it was necessary to look for alternative raw materials to replace it. The aroma of betel leaf is still too dominant so it was necessary to find the right composition.